Reframing Latin America : a cultural theory reading of the nineteenth and twentieth centuries - Ching, Erik Kristofer (University of Texas Press, 2007)
Providing an extensive introduction to cultural studies in general, regardless of chronological or geographic focus, and presenting provocative readings from Latin American writers of the last two centuries, this title brings much needed accessibility to the concepts of cultural studies and postmodernism.